Supply Chain Integration Enables Resilience, Flexibility, and Innovation to Improve Business Performance in COVID-19 Era - Hotlan Siagian (Sustainability, 2021)
The COVID-19 pandemic has brought about a sudden change from normal conditions to disruption conditions, and industrial sectors have experienced eroded growth. In particular, the manufacturing industry experienced a slowdown due to the sudden disruption in supply and demand. This situation stimulates the manufacturing industry to recover from this current challenging disruption. This study investigates the impact of supply chain integration on business performance through supply chain resilience, supply chain flexibility, and innovation system in Indonesia’s manufacturing companies. Data collection has obtained as many as 470 questionnaires considered valid for further analysis. Data analysis used the partial least square (PLS) technique using smartPLS software version 3.0. The results show that supply chain integration affects innovation system, supply chain flexibility, and supply chain resilience because of its ability to share complete product information and share production planning. Innovation systems and supply chain flexibility enhance supply chain resilience through the ability to deal with sudden changes in customer demand and production problems. Supply chain integration improves business performance through innovation, supply chain flexibility, and supply chain resilience in the COVID-19 era. This research could be the best practice for managers in restoring manufacturing performance quickly. This study also contributes to the current research in supply chain management.